Differences in Student Learning Outcomes Using the Game Based Learning Model Assisted with Wordwall Media and The Cooperative Learning Model - Safitri, Dayinta Briliana; Sukidin (Asian Journal of Multidisciplinary Studies, 2024)
Learning success is influenced by several components such as models, methods, media, and learning outcomes. Some learning models that can be applied in the classroom are game-based learning and cooperative learning. To support the implementation of the learning model, teachers need media such as the Wordwall game quiz. This research aims to determine the differences in student learning outcomes between word wall-assisted game-based learning and cooperative learning models in class X of SMAN Jenggawah, Jember Regency, academic year 2023/2024. The population taken in this research was class X at SMAN Jenggawah Jember. The research method used in this research is quasi-experimental with a nonequivalent control group design. The samples taken in this research were X-1 and X-3, each class consisting of 36 students. The sampling technique uses purposive sampling. The technique used in collecting learning outcomes data is a test which is divided into 2, namely pre-test and post-test. The results of the data analysis show that the results of the normality test in the control class obtained a significance value of 0.335 in the pretest and 0.088 in the posttest. The results of the normality test in the experimental class obtained a significance value of 0.096 in the pretest and 0.787 in the posttest. It can be concluded that all data is normally distributed. Based on the results of the normality test, a hypothesis test is then carried out, namely a difference test using the Independent Sample T-Test. Based on the data from the hypothesis test results, it can be seen that the significance value (2-tailed) is <0.05, namely 0.000. It can be concluded that there were differences in economic learning outcomes between students who were given learning using the game-based learning model assisted by Wordwall media and students who were given learning using the cooperative learning model in class X students at SMAN Jenggawah, Jember Regency.